CORPORATE GOVERNANCE IN OECD MEMBER COUNTRIES - Alina HAGIU; Marinela BARBULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Corporate governance reflects how a company is managed and controlled. In defining this concept it goes on the idea that the global performance of the company is based on the theory of interest holders. The value of the firm is maximized to the extent that managers manage to identify and harmonize conflicts of interest that arise between the company's social partners, especially between shareholders and managers. Harmonization of these interests is ensured through the corporate governance system. In this paper we aim to analyze the corporate governance in the OECD member countries with a focus on the rights of shareholders and key ownership functions.